(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
Elections are one of the mechanisms that involve society to participate in government. In its history, Indonesia has been running elections since 1955, with the ever-changing arrangements that follow. Finally in Constitutional Court Ruling Number 55/PUU/XVII/2019 decided to hold the elections simultaneously both at the national level and the local level with some elective models. In this study the authors are trying to formulate how to select the best simultaneous elections to implement them accordingly. This research is a normative study with a descriptive nature of research. The approach of the authors in the study is the Statue approach, the conceptual approach, the historical approach, the analytical approach, and the comparative approach.